Design of Automatic Sensor Equipped Shower - Mohamad, Mahmod Abd Hakim; Yahaya Ramli,; Mohamad Fadzli Amin, Mohamad Faris Aiqal; Ismail, Mohamad Shahrolnizam; Ismail, Muhammad Faizal (Multidisciplinary Applied Research and Innovation, 2022)
The automatic sensor equipped shower is a project that has been carried out by our team because it can bring mana benefits toward the user and environment. The objective for this project is to reduce time taken in every bath, save the usage of water in daily life by increase its efficiency in every shower taken and avoiding the shower to respond to false signal by adding bluetooth technology. The project scope is to add the Bluetooth technology into the shower system to increase the efficiency and provide a new way for people to use shower and optimize the usage of shower by adding bluetooth technology. Method that has been used include simulation in several software and consideration on material for each part of the project is selected based on the engineering properties, cost, market availability, and durability. According to the google form survey that has been shared, most respondents seems to agree with the project design and its features. In the future, some improvement can be made in order to suit our project with the market needs.